2021
DOI: 10.3390/children8060493
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Surfactant for Preterm Infants with Respiratory Distress Syndrome

Abstract: Currently, the administration of surfactant to preterm infants with respiratory distress syndrome (RDS) mainly relies on intratracheal instillation; however, there is increasing evidence of aerosolized surfactant being an effective non-invasive strategy. We present a historical narrative spanning sixty years of development of aerosolization systems. We also offer an overview of the pertinent mechanisms needed to create and manage the ideal aerosolization system, with a focus on delivery, distribution, depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…At present, surfactant treatment of premature infants with respiratory distress syndrome (RDS) depends on intratracheal instillation, either by tracheal intubation in combination with mechanical ventilation or by less invasive surfactant administration (LISA) via a thin intratracheal catheter during NIV [ 7 ]. However, efficacy of aerosol delivery of surfactant depends not only on the composition of the surfactant formulation, its safety and efficacy, but also on the type of aerosolization device and non-invasive interface used, and the possibility to synchronize surfactant delivery with spontaneous breathing [ 16 ]. Three recent clinical studies have shown that non-invasive aerosol delivery of animal-derived surfactant can prevent the need for early intubation [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, surfactant treatment of premature infants with respiratory distress syndrome (RDS) depends on intratracheal instillation, either by tracheal intubation in combination with mechanical ventilation or by less invasive surfactant administration (LISA) via a thin intratracheal catheter during NIV [ 7 ]. However, efficacy of aerosol delivery of surfactant depends not only on the composition of the surfactant formulation, its safety and efficacy, but also on the type of aerosolization device and non-invasive interface used, and the possibility to synchronize surfactant delivery with spontaneous breathing [ 16 ]. Three recent clinical studies have shown that non-invasive aerosol delivery of animal-derived surfactant can prevent the need for early intubation [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…52 Animal and human studies have shown that the dosage range of 50-200 mg/kg AS has resulted in improved lung gas exchange. 53-55 Studies have shown that redosing requirement decreased with the use of the initial higher concentration of surfactant. Comparison of high dose (200 mg/kg) versus low dose (100 mg/kg) of poractant alfa has shown that a high initial dose of surfactant was associated with lesser need for retreatment (odds ratio (OR) 0.93; 95% CI 0.90-0.96) when administered via less invasive surfactant administration (LISA) and intubate surfactant extubation (InSurE) and shorter duration of oxygenation and MV support (OR 0.92; 95% CI, 0.90-0.95) (with LISA only, not with InSurE) compared with initial low-dose surfactant.…”
Section: Dosing and Redosing Of Surfactantmentioning
confidence: 99%
“…52 Animal and human studies have shown that the dosage range of 50-200 mg/kg AS has resulted in improved lung gas exchange. [53][54][55] Studies have shown that redosing requirement decreased with the use of the initial higher concentration of surfactant. [56][57][58] Porcine surfactant preparation has also shown decrease in retreatment requirement compared with bovine surfactant.…”
Section: Dosing and Redosing Of Surfactantmentioning
confidence: 99%
“…During the last decades, attempts to treat RDS with aerosolized surfactant using different nebulization methods failed to prove the undisputed effectiveness of this method. Only recently, randomized clinical studies using modern nebulization methods demonstrated the feasibility and effectiveness of aerosolized surfactant nebulization in preventing intubation and mechanical ventilation [54]. The study by Cummins et al that enrolled 457 neonates with a wide range of GA (23 to 41 weeks, median 33 weeks) showed that in neonates with mild-moderate respiratory distress, aerosolized surfactant decreased the intubation rate and surfactant instillation by 50% [55].…”
Section: Use Of Nebulized Surfactantmentioning
confidence: 99%